STUDENTS’ LEARNING ENTHUSIASM THROUGH BLOOKET ON THE TOPIC OF STEP FUNCTIONS AT MAN KOTA SURABAYA - Farhah Malihatus Sholihah; Agus Prasetyo Kurniawan; Wahyuni Fajar Arum (Jurnal Prinsip Pendidikan Matematika, 2026)
The low enthusiasm of students towards mathematics learning, particularly on the abstract topic of step functions, necessitates the innovation of learning media that can increase students' attention and engagement. One effort to address this is by implementing interactive learning media based on digital games, such as Blooket. This media is believed to enhance students' attention, interest, active participation, and emotional involvement during the learning process. This study aims to analyze the level of learning enthusiasm of 11th-grade students at MAN Kota Surabaya through the application of interactive Blooket media in mathematics learning. The method used is a quantitative descriptive approach, with 27 students selected using a saturated sampling technique. The research instruments include a learning enthusiasm questionnaire, observation, and documentation. The research results show that the use of Blooket media is able to increase students' learning enthusiasm with an average percentage of 85.53%, which falls into the very high category. These findings indicate that game-based interactive media is effective in enhancing students' attention, interest, active participation, and emotional engagement. This media is recommended as an alternative for innovative digital-based mathematics learning.